REINTERPRETASI TERHADAP PEMAHAMAN HADITS-HADITS TENTANG GENDER DALAM PERSPEKTIF FIQH AL-HADITS - zailani zailani; Kaizal Bay; Sri Chalida (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
There are a lot of hadiths that influenced certain circumstances, especially those “degrading” degrees of women. If the hadiths are textually practiced, there would certainly be an impact on human-right violations. If broken, it will also affect the person’s faith in applying the traditions of Prophet SAW in his life. This issue certainly needs the best solution in understanding these hadiths. It is unneglectable to avoid that women harassment are still happening today. Everyone witnesses that so many women lost their rights, both as a human being, such as subordinated to its shortcomings, but also as citizens, such as loss of right to be a leader. The women with this particular plight are the result of men’s behavior who stand on religious arguments (especially hadith) that put women as “humbled” and even simply as the creature that confined to live in walls of house, which is just back and forth between the kitchen, wells and mattresses. Reinterpretation of Islamic concepts on the position of women should be provided in order to give opportunity to the present women as highly dynamic, courteous, and beneficial for religion and society. We all believe that Prophet Muhammad SAW was the great personal who respected and uphold the honor of women. This is the gap between the will of the Prophet SAW with the understanding of Muslim believers about the hadiths of the Prophet SAW